Enhancement in a brain glioma model: A comparison of half‐dose gadobenate dimeglumine versus full‐dose gadopentetate dimeglumine at 1.5 and 3 T. Issue 2 (4th June 2013) - Morelli, John N.; Gerdes, Clint M.; Zhang, Wei; Williams, Jonathon M.; Saettele, Megan R.; Ai, Fei
<x xml:space="preserve">Abstract</x> Purpose To examine dose reduction comparing enhancement with full‐dose gadopentetate dimeglumine (0.1 mmol/kg) to half‐dose gadobenate dimeglumine in a rat brain glioma model. Materials and Methods Intra‐axial parenchymal brain tumors were implanted in 17 experimental animals. The 13 surviving animals were imaged at 1.5 or 3 T. Either gadopentetate dimeglumine or gadobenate dimeglumine was injected in random order on consecutive days. Tumor signal‐to‐noise ratio (SNR), contrast‐to‐noise ratio (CNR), and contrast enhancement (CE) for each agent were obtained with region of interest analyses and compared. Lesions were confirmed histopathologically. Results Statistically significantly lower SNR, CNR, and CE parameters were found at both 1.5 and 3 T with half‐dose gadobenate dimeglumine relative to full‐dose gadopentetate dimeglumine (P < 0.05). SNR on average at 3 T was 70.0 ± 14.4 for gadopentetate dimeglumine and 57.0 0 ± 4.8 for gadobenate dimeglumine (P < 0.02). Conclusion Improved r1 relaxivity with gadobenate dimeglumine does not produce adequate half‐dose contrast‐enhancement relative to full‐dose gadopentetate dimeglumine. J. Magn. Reson. Imaging 2013;38:306–311. © 2012 Wiley Periodicals, Inc.